Markets and climate are driving rapid change in farming practices in Savannah West Africa - Ouédraogo, Mathieu; Zougmoré, Robert B.; Moussa, Abdoulaye S.; Partey, Samuel T.; Thornton, Philip K.; Kristjanson, Patricia M.; Badiane Ndour, Ndèye Yacine; Somé, Léopold; Naab, Jesse B.; Boureima, Moussa; Diakite, L.; Quirós, Carlos F. (Springer, 2017)
Agricultural practices have constantly changed in West Africa, and understanding the factors that have driven the changes may help guide strategies to promote sustainable agriculture in the region. To contribute to such efforts, this paper analyzes drivers of change in farming practices in the region using data obtained from surveys of 700 farming households in five countries (Burkina Faso, Ghana, Mali, Niger and Senegal). The results showed that farmers have adopted various practices in response to the challenges they have faced during the last decade. A series of logit models showed that most changes farmers made to their practices are undertaken for multiple reasons. Land use and management changes including expanding farmed areas and using mineral fertilization and manure are positively related to perceived changes in the climate, such as more erratic rainfall. Planting new varieties, introducing new crops, crop rotation, expanding farmed area and using pesticides are positively associated with new market opportunities. Farm practices that require relatively high financial investment such as use of pesticides, drought-tolerant varieties and improved seeds were positively associated with the provision of technical and financial support for farmers through development projects and policies. Changes in markets and climate are both helping to promote needed changes in farming practices in West Africa. Therefore, policies that foster the development of markets for agricultural products, and improved weather- and climate-related information linked to knowledge of appropriate agricultural innovations in different environments are needed.